Checklist of Aquatic Heteroptera genera (Insecta: Hemiptera) from Brazilian Savanna (Cerrado Biome), with family and genera identification key - Martins-Silva, Maria Julia (EntomoBrasilis, 2022)
Insects of the order Hemiptera (Heteroptera) are considered the largest group of insects with incomplete metamorphosis. Representatives of the Gerromorpha and Nepomorpha infraorders are found in the Brazilian Savanna (Cerrado Biome). This manuscript provides information about the occurrence and distribution of families and genera that occur in the states of the Cerrado Biome, deposited in the UnB Aquatic Invertebrate Collection (CIAq-UnB). The collection started in 1995 and have aquatic specimens of Cerrado Biome. An identification key is also presented for the families and genera that occur in this region.